Different bonds around plutonium: Physicists' and freelance journalists' tweets at the time of the 3/11 nuclear crisis. (June 2019) - Inako, Ayumi
Highlights: A community is discursively negotiated via patterned coupling of experience and values. Twitter communication at the 3/11 nuclear crisis involved uncertainty intrinsic to science. The community that emerged around physicists focused on accurate understanding of the accident. The community that emerged around freelance journalists foregrounded accusation toward the authorities. Disaster/crisis communication on social media entails tension between information-sharing and communion. Abstract: This paper examines divergent Twitter communities that formed around tweeters from two distinct professional groups, physicists and freelance journalists, during the immediate aftermath of the 2011 nuclear accident in Fukushima, Japan. It was a time when a heightened level of anxiety was accompanied by mistrust toward "official" information disseminated in the mainstream media that required highly technical scientific knowledge to interpret. This paper draws on systemic functional linguistics (SFL), in which community is conceptualized in terms of patterns of "couplings" of ideational and interpersonal meanings, to carry out an analysis of the linguistic choices through which these different communities that formed during crisis shaped themselves. In one community, a focus on knowledge was dominant, while in the other a focus on values was dominant. This contrast is discussed in terms of a tension between two fundamental social needs entailed in communicating news of a disaster: information-sharing and communion.